Pharyngeal motility in patients submitted to type I thyroplasty - Bruno Rezende Pinna; Fernando A.M. Herbella; Noemi de Biase (Brazilian Journal of Otorhinolaryngology, 2021)
Introduction: Type 1 thyroplasty is performed to improve glottis closure as well as dysphagic symptoms in patients with unilateral vocal fold immobility. Objectives: This study aims to compare the motility of the pharynx and upper esophageal sphincter in patients with unilateral vocal fold immobility before and after thyroplasty Type I. Methods: We prospectively studied 15 patients with unilateral vocal fold immobility who underwent thyroplasty Type I. Subjects were divided according to the topography of vagal injury and presence of dysphagia. High resolution manometry was performed before and 30 days after surgery. Time and pressure manometric parameters at the topography of the velopharynx, epiglottis and upper esophageal sphincter were recorded. Results: Dysphagia was present in 67% of patients. 63% had lower vagal injuries. Manometric parameters did not change after thyroplasty for the whole population. The group of dysphagic patients, however, had an increase in residual pressure at the upper esophageal sphincter after thyroplasty (1.2 vs. 5.2 mmHg; p = 0.05). Patients with low vagal injury developed higher peak pressure (100 vs. 108.9 mmHg p ≤ 0.001), lower rise time (347 vs. 330 ms p = 0.04), and higher up stroke (260 vs. 266.2 mmHg/ms p = 0.04) at the topography of the velopharynx after thyroplasty. Conclusion: Pharyngeal motility is affected by thyroplasty Type I in patients with dysphagia and low vagal injury.